Intolerance of uncertainty predicting work performance of indonesian temporary employees mediated by personal initiative - Yuniardi, Muhamad Salis; Cant, Matthew; Putri, Aransha; Amalia, Andi Nanda; Arumbiya, Salsabila (University of Muhammadiyah Malang, 2023)
Temporary employees in Indonesia have less certainty over their recent and prospective careers. This study aims to investigate whether the Intolerance of Uncertainty (IU) may predict personal initiative (PI) and subsequently affect work performance (WP). It was hypothesized that there was a direct and indirect relationship between IU and WP, through the PI. The Purposive sampling technique was utilised in this research. The sample comprised 153 temporary employees who have been working in their current contract for more than six months Data was gathered through The Intolerance of uncertainty-12 items, Personal Initiative Scale, and Individual Work Performance Questionnaire and analyzed through Mediation analysis from PROCESS. The result reveals that IU does not have a direct relationship to WP (effect = -0.1450, p = .187), however, IU indirectly predicts WP through PI (effect = -0.1510, LLCI = -0.3251, ULCI = -0.0079). Temporary employees who report higher IU will have less PI (effect = -0.1254, p =0.0259), and eventually, their work performance will decrease (effect = 1.2042, p < 0.001). This research has some implications. First, during the employees’ recruitment process, the organisation need to consider the IU as a predictor of WP, and the government need to ensure that the companies abide by the Indonesian Labour Law – Act 13 of 2003 related to employees' welfare.